Hear #metoo in India : news, social media, and anti-rape and sexual harassment activism - Guha, Pallavi (Rutgers University Press, 2021)
This book examines the role media platforms play in anti-rape and sexual harassment activism in India. Including 75 interviews with feminist activists and journalists working across India, it proposes a framework of agenda-building and establishes a theoretical framework to examine media coverage of issues in the digitally emerging Global South.
Keywords: Rape victims -- India.; Sexual harrassment -- India.; Sexual abuse victims -- India.; Women -- Violence against -- India.; Women -- Political activity -- India.; Feminism -- India.; Victimes de viol -- Inde.; Victimes d'abus sexuels -- Inde.; Femmes -- Violence envers -- Inde.; Femmes -- Activité politique -- Inde.; Féminisme -- Inde.; SOCIAL SCIENCE / General.; Feminism; Rape victims; Sexual abuse victims; Women -- Political activity; Women -- Violence against; India; #metoo, India, Anti-rape, Rape culture, Sexual Harassment, Feminism, Activism, Global South, Time magazine, #metoo movement, social media, mainstream, mass media, Cultural Studies, Media, Journalists, Public Policy, Urban Region, Rural Region.